Ergonomic analysis on wheelchair redesign to improve user health and safety - Kusmindari, Christofora Desi; Pasmawati, Yanti; Arfianto, Ahmad Syahrul; Pratama, Muhammad Rezky Putra; Prassetio, Rendi (Universitas Mercu Buana, 2025)
This research aims to redesign a wheelchair to enhance comfort and safety based on the ergonomic needs of users through a holistic ergonomic approach. The study employs the FMEA (Failure Mode and Effects Analysis) method to identify product failures in wheelchairs and determine preventive measures using the Risk Priority Number (RPN), calculated from Severity (S), Occurrence (O), and Detection (D). A biomechanical assessment using REBA (Rapid Entire Body Assessment) evaluates the posture and movements of wheelchair users and identifies factors contributing to ergonomic risks. The FMEA analysis revealed three failure modes with the highest RPN values: